Internalization of Personal Educational Values based on the Interests and Talents of Students at Islamic Boarding School - Hendra Irwandi; Zulhimma Zulhimma (TATHO: International Journal of Islamic Thought and Sciences, 2026)
ABSTRACT The transformation of Islamic education in the digital era demands a learning model that is not only academically oriented but also capable of developing students' personal potential. This study aims to describe the instilling of personal education values based on the talents and interests of Islamic boarding school students through the “Santri Dream Roadmap” program at the Darul Mursyid Islamic Boarding School. The study used reflective qualitative methods through observation, interviews, participatory workshops, and community engagement. The results show that this program increases students' self-awareness and motivation, transforms the role of teachers into reflective mentors, and strengthens the synergy between the Islamic boarding school and families. The main contribution of this study is to offer an implementable framework for Personal Education that is integrated with Islamic values ​​and relevant to the demands of 21st-century education. This model can be replicated by other Islamic boarding schools seeking to develop a personalized and character-based learning approach.